Fredholm and Schatten Class Operators on Bergman Spaces with Exponential Weights - Xuedi Ma; Xiaofeng Wang; Jin Xia (Journal of Function Spaces)
In this paper, we give a characterization of Fredholmness of the Toeplitz operators on the Bergman spaces Aφp with exponential weights in D when 0<p<∞. Also, we obtain the sufficient and necessary conditions which the Toeplitz and Hankel operators on Aφ2 belong to h-Schatten class, where h is a continuous increasing convex function.